2022
DOI: 10.1186/s12974-022-02578-9
|View full text |Cite
|
Sign up to set email alerts
|

Human PMSCs-derived small extracellular vesicles alleviate neuropathic pain through miR-26a-5p/Wnt5a in SNI mice model

Abstract: Background Mesenchymal stem cell (MSCs)-derived small Extracellular Vesicles (sEVs) are considered as a new cell-free therapy for pain caused by nerve injury, but whether human placental mesenchymal stem cell-derived sEVs relieve pain in sciatic nerve injury and its possible mechanism are still unclear. In this study, we investigated the roles of hPMSCs-derived sEVs and related mechanisms in neuropathic pain. Methods The spared nerve injury (SNI) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 71 publications
1
10
0
Order By: Relevance
“… 49 In this regard, another study showed that a single intrathecal injection of the human placental mesenchymal stem cells (hPMSCs)-derived small extracellular vesicles durably reversed mechanical hypersensitivity and neuroinflammation through miR-26a-5p/Wnt5a in mice with partial sciatic nerve ligation. 50 Histological and functional evaluation of the crushed sciatic nerve after transplanting the gel containing human multipotent mesenchymal stromal cell-derived extracellular vesicles (MSCs-EVs) showed a significant decrease in apoptotic neuronal death and an increase in regeneration-associated proteins NF-200 and GAP-43, as well as a decrease in muscle atrophy. 51 Exosomes from Lipopolysaccharide (LPS)-preconditioned mesenchymal stem cells accelerated functional recovery, axon regeneration and remyelination through proinflammatory macrophage-to-progenitor macrophage transition.…”
Section: Methodsmentioning
confidence: 99%
“… 49 In this regard, another study showed that a single intrathecal injection of the human placental mesenchymal stem cells (hPMSCs)-derived small extracellular vesicles durably reversed mechanical hypersensitivity and neuroinflammation through miR-26a-5p/Wnt5a in mice with partial sciatic nerve ligation. 50 Histological and functional evaluation of the crushed sciatic nerve after transplanting the gel containing human multipotent mesenchymal stromal cell-derived extracellular vesicles (MSCs-EVs) showed a significant decrease in apoptotic neuronal death and an increase in regeneration-associated proteins NF-200 and GAP-43, as well as a decrease in muscle atrophy. 51 Exosomes from Lipopolysaccharide (LPS)-preconditioned mesenchymal stem cells accelerated functional recovery, axon regeneration and remyelination through proinflammatory macrophage-to-progenitor macrophage transition.…”
Section: Methodsmentioning
confidence: 99%
“…Of note, however, in contrast to the effect of Ift88 siRNA in control rats, which increased baseline mechanical nociceptive threshold in naïve control rats, inhibitors of Hh signaling in the absence of inflammation or peripheral neuropathy did not affect nociceptive threshold, supporting the presence of an Hh-independent primary cilium function capable of regulating baseline mechanical nociceptive threshold. Another primary cilium-dependent cellular signaling pathway that has been found to contribute to nociception is the wingless-related integration site (Wnt)/b-catenin signaling pathway [89][90][91][92][93][94][95] . Ciliary proteins are not only necessary for the regulation of certain types of Wnt signaling but also include effectors downstream of Wnt [96][97][98][99] .…”
Section: Shh Enhances Calcium Oscillations In Embryonic Neuronsmentioning
confidence: 99%
“…Elevated expression of miR-155-5p in the spinal cord contributed to mechanical hypersensitivity via the microglia inflammatory response of microglia in rats with bone cancer pain [ 9 ]. Furthermore, Miat promotes nerve injury-induced chronic pain through the miR-362-3p/BAMBI signaling axis pathway [ 10 ], and human placental mesenchymal stem cell-derived small extracellular vesicles have alleviated neuropathic pain via miR-26a-5p/Wnt5a in a mouse model of the spared nerve injury [ 11 ]. These studies indicated a tight association between miRNAs and neural pain.…”
Section: Introductionmentioning
confidence: 99%